Was Rooming-In a Safe Approach to Newborns from SARS-Cov-2 Positive Mothers? - Joana Jonet (Sociedade Portuguesa de Pediatria, 2021)
Introduction: Since the emergence of coronavirus disease 2019 (COVID-19) there are limited data describing the risks and specific effects of SARS-CoV-2 in pregnant women and their neonates. To date, there is scarce evidence of in utero transmission, and the risk of perinatal transmission and consequent neonate’s risk of developing COVID-19 during the perinatal period are also unknown.